An Account of the controversy surrounding the denial of University recognition to the chapter of the Students for a Democratic Society at Wisconsin State University - La Crosse - Finn, James E. (My University, 1970)
In Deccmber of 1966, Samuel G. Gates, President of Wisconsin State University -La Crosse, denied university recognition to the Students for a Democratic Society (SDS). This action provoked a heated public controversy and a legal contest which culminated in a rathcr oblique judicial decision. In addition, considerable confusion existed as to the exact meaning of university policies concerning the effects of non-recognition. The text of this paper consists of an account of the various aspects of this controversy. This essay was written primarily from documents pertaining to the events described therein. This material was supplemented by conversations with various university officials in regard to interpretation of university policies toward SDS. Every effort was made to provide an objective account of the SDS controversy based on the information gathered. The findings of the study may be described as descriptions of the various positions and actions of the participants in the controversy. Because of the nature of the topic and the author's desire to provide a factual account of the events described, no attempt was made to draw inferences or conclusions concerning any aspect of the controversy.
Keywords: College students -- Wisconsin -- La Crosse -- Political activity; Radicalism -- Wisconsin -- La Crosse; Wisconsin State University (La Crosse) -- Students -- Political activity; Students for a Democratic Society (U.S.) -- La Crosse Chapter